The WTO Global Trade Model: Technical documentation - Angel Aguiar; Erwin L. Corong; Dominique van der Mensbrugghe; Eddy Bekkers; Robert Bernard Koopman; Robert Teh (World Trade Organization (WTO), 2019)
This document provides a technical description of the WTO Global Trade Model developed by the Center for Global Trade Analysis (GTAP) and the World Trade Organization (WTO). The model can be used to generate global trade projections and to assess the medium and long run effects of a wide range of global and national trade policies. The WTO Global Trade Model is a recursive dynamic extension of the static GTAP model (Corong et al., 2017), and implements a parsimonious approach to incorporate monopolistic competition - i.e., Eithier-Krugman or Melitz-type firm heterogeneity - in the standard GTAP model following Bekkers and Francois (2018).
Keywords: C68; F12; F17; 330; computable general equilibrium; recursive dynamics; baseline projections; international trade